الصناعات الإبداعية وعائداتها الاقتصادية والاجتماعية والثقافية على المجتمع )رؤية مستقبلية( - همت, محمد يوسف عبد العزيز; عبد الوهاب, جودة الحايس (Sciences de l'Homme et de la Société; No 25 (2017): مجلة علوم الإنسان والمجتمع, 2017)
تناول البحث الراهن العوائد المتعددة للصناعات الإبداعية. وجاءت أهمية البحث من التحولات التى تحدث على صعيد الاقتصاد العالمى والذى يتجه نحو سبل جديدة للتنمية تقوم على آليات ترتكز على المعرفة والإبداع والابتكار والتكنولوجيا فى إطار ما يعرف باقتصاد المعرفة" الاقتصاد الإبداعى. وخرج البحث ببعض المقترحات لتعزيز الصناعات الإبداعية فى الدول النامية منها: الإستثمار في التعليم ورأس المال البشرى، وفى الأصول الثقافية المحلية، وتعزيز الابتكار وتشجيع المشروعات الصغيرة والمتوسطة. Abstract: The current research addressed the multiple returns of creative industries. the importance of research came from the transformations occurring in the global economy moving towards new ways of development is based on mechanisms based on knowledge, creativity, innovation and technology within the knowledge economy"creative economy". The research has produced some proposals to promote creative industries in developing countries, including: investment in education, human capital, local cultural assets, promotion of innovation and small and medium-sized enterprises.